Knowledge management: contribution to Management University in Cuba - Medina-Nogueira, Daylin (2014)
The work deals with a set of repositories to enable researchers and teachers with managing their scientific work. Repositories dissertation, master's, undergraduate were performed; books, magazines, among others. The bulletin "for Knowledge Management" was held to disseminate scientific results achieved in Cuban business studies.